2002
DOI: 10.1055/s-2002-36709
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprolactinemia: Etiology, Diagnosis, and Management

Abstract: Hyperprolactinemia is the most common endocrine disorder of the hypothalamic-pituitary axis. A prolactinoma is the most common cause of chronic hyperprolactinemia once pregnancy, primary hypothyroidism, and drugs that elevate serum prolactin levels have been excluded. Patients can present with hypogonadism, infertility, galactorrhea, osteopenia, and mass effects of the tumor. When hyperprolactinemia is confirmed, a cause for the disorder needs to be sought. This involves a careful history and examination, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
79
1
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 37 publications
1
79
1
4
Order By: Relevance
“…Selective degeneration of DA neurons in the SN but not in the VTA or the hypothalamus leads to Parkinson's disease (PD) (3)(4)(5)(6)(7), whereas abnormal function of the VTA DA neurons has been linked to schizophrenia, attention deficit, addiction, and hyperactivity disorders (8)(9)(10)(11). In addition, dysfunction of hypothalamic DA neurons can cause hyperprolactinemia, an endocrine disorder of the reproductive system (12), whereas changes in the activity of the NA system have been linked to depression as well as sleep disorders (13,14).…”
mentioning
confidence: 99%
“…Selective degeneration of DA neurons in the SN but not in the VTA or the hypothalamus leads to Parkinson's disease (PD) (3)(4)(5)(6)(7), whereas abnormal function of the VTA DA neurons has been linked to schizophrenia, attention deficit, addiction, and hyperactivity disorders (8)(9)(10)(11). In addition, dysfunction of hypothalamic DA neurons can cause hyperprolactinemia, an endocrine disorder of the reproductive system (12), whereas changes in the activity of the NA system have been linked to depression as well as sleep disorders (13,14).…”
mentioning
confidence: 99%
“…Moreover, removal and examination of level l and level ll lymph nodes yields desired results due to axillary dissection; Table 4A: Number of metastatic and non metastatic total lymph node and distrubition in Tc 99m sulfur colloid group. however, the morbidity is close to that of complete axillary dissection when it is performed with radiotherapy (17). The number of lymph nodes removed during axillary dissection depends on a number of factors, most notably the extent of dissection.…”
Section: Discussionmentioning
confidence: 97%
“…In other studies, the prevalence of hyperprolactinemia varied from approximately 0.2% in an unselected normal adult population to 15%-20% among women with reproductive disorders, whereas a study of women with a wider age range (15-45 years) found that 61% of patients with abnormal bleeding had hyperprolactinemia, whereas in our study only 18% of patients with abnormal uterine bleeding had hyperprolactenemia and 2% of women without abnormal uterine bleeding had hyperprolactenemia. [24][25][26] Most of thegynaecologists today will investigate for prolactin levels only among patientswith symptoms of galactorrhea or galactorrhea associated with oligomenorrhea or amenorrhea. In the current study, galactorrhea was present in 18% of the patients with AUB overall.…”
Section: Discussionmentioning
confidence: 99%